Using the Right to Health to Advance Equitable Universal Health Coverage in Uganda's National Health Insurance Scheme Bill. Issue 2 (May 2022) - Forman, Lisa; Uberoi, Diya; Mulumba, Moses
Abstract : In 2019, the Ugandan government issued the National Health Insurance Scheme (NHIS) Bill to promote more equitable access to health care, passing this Bill in March 2021. While the NHIS marks a significant step towards equitable reform of the health system, it also raised concerns about its impact on equity and the right to health. This article considers the extent to which the proposed 2019 Bill is in line with the right to health in international and Ugandan law, and offers recommendations to strengthen the foundation it sets for future and more equitable health policy.